Transmission in interprofessional humanitarian teamwork: a scoping review - Galaad Lefay; Pierre-Yves Therriault; Catherine Delgoulet (Journal of International Humanitarian Action)
Abstract Context Since the end of the 1990s, the humanitarian sector lives a process of professionalization which has created some challenges for organizations and workers. These changes, which aim to standardize and harmonize practices, have also added issues of worker retention, creation of intercultural and interprofessional teamwork, skills development, health, and maintaining expertise in the fields. Aim Identify the mechanisms of knowledge transmission within humanitarian intervention collectives in a professionalization context. Method The design follows the five-step scoping analysis method proposed by Arksey and O’Malley (Int J Soc Res Methodol 8:19-32, 2005). Results The study examines dynamics within humanitarian work groups, focusing on relations between international and national workers, professional segmentation, and collective resilience. It also explores essential knowledge in humanitarian work (contextual, technical, collaborative, metacognitive, and managerial) and the main modes of knowledge transmission: reflective practices, on-the-job transmission, and training. Understanding these interactions and transmissions optimizes effectiveness and skill development in humanitarian contexts. Discussion/conclusion This article discusses professionalization through the rationalization of the humanitarian sector. There is a lack of scientific interest in knowledge transmission through work groups, with a focus on training programme evaluation. Existing dynamics on the ground is harder to control, hindering the evaluation of investment effectiveness. This trend is accompanied by a scarcity of field studies. In addition, there is a need for collective adaptation to respond to unusual situations. However, professionalization, subject to the constraints of donors, can create difficulties for non-governmental organizations (NGO) to establish conditions conducive to resilience or innovation. Our findings call on policy-makers to support adaptable frameworks that improve knowledge sharing and team dynamics in humanitarian response.